2022
DOI: 10.3390/ijerph192214990
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Tumor Boards on Breast Cancer Care: Evidence from a Systematic Literature Review and Meta-Analysis

Abstract: Breast cancer is the most common malignancy in women, with a complex clinical path that involves several professionals and that requires a multidisciplinary approach. However, the effectiveness of breast cancer multidisciplinary care and the processes that contribute to its effectiveness have not yet been firmly determined. This study aims to evaluate the impact of multidisciplinary tumor boards on breast cancer care outcomes. A systematic literature review was carried out through Scopus, Web of Science and Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(168 reference statements)
0
2
0
Order By: Relevance
“…In oncology, the evidence of the apparent benefit was initially difficult to demonstrate. However, time and further studies have shown the benefits of the MDT approach in several oncology subdisciplines [13,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In oncology, the evidence of the apparent benefit was initially difficult to demonstrate. However, time and further studies have shown the benefits of the MDT approach in several oncology subdisciplines [13,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, involvement of experts in the respective field is considered a key element to successful treatment. In oncology, tumor boards have been established and proven to be a useful tool to improve treatment in terms of reduced mortality by discussing cases in a multidisciplinary setting [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most diagnosed malignancy in women. In 2020, 2.3 million new cases of breast cancer were estimated, and there were 683,000 deaths from this disease, while approximately 7.8 million women were alive with a diagnosis of breast cancer [ 1 ]. In Italy, in 2020, approximately 55,000 new diagnoses of breast cancer and approximately 12,300 deaths were estimated; in addition, more than 834,000 women diagnosed with breast cancer were alive.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the incidence increases until menopause and then slows down after, and starts to rise again after the age of 60 [ 2 , 3 ]. The risk factors include age, reproductive factors, hormonal factors, dietary and metabolic factors, previous thoracic radiation therapy, previous dysplasia or breast cancer, family history, and genetic factors [ 1 ].…”
Section: Introductionmentioning
confidence: 99%